The Influence of Attitudes and Work Abilities on Service Quality at the Legal Metrology UPTD of the Trade and Industry Service of Gowa Regency - Damayanti, Damayanti; Sherry Edelia; Natsir Kalla (CV. AFDIFAL MAJU BERKAH, 2024)
This research is a type of quantitative research with the aim of knowing and analyzing